Asessing the Impacts of Paradiplomacy on Batam-Singapore Cooperation: A Case Study in Tourism, Economic Growth, and Infrastructure Development - Abdi, Rangga Putra (Universitas Muhammadiyah Yogyakarta, 2023)
Paradiplomacy is a concept that enables sub-national entities to establish relationships with counterparts in other countries. One form of paradiplomacy is sister cities, where local governments of one country collaborate with regional governments from other countries to jointly develop their respective regions. The partnership between Batam and Singapore City as sister cities focuses primarily on promoting tourism, while also enhancing cooperation in the development of Batam across various sectors, such as investment, transportation, tourism, labor, and agribusiness. Additionally, they collaborate on projects like the development of Funtasy Island. This research adopts a qualitative methodology, drawing from a range of sources, including research articles, journals, and the latest news updates from all involved parties. The theory of international cooperation is applied to establish correlations between the concepts of paradiplomacy and sister cities, aligning with the study's objectives and discussion. Batam's paradiplomacy efforts operate within the scope of Indonesia's Free Trade Zone (FTZ). Notably, investment emerges as a key focal point, with Batam selected as a primary and priority target for future investments in the region.